Incidence of contralateral regional failure in the electively irradiated contralateral neck of patients with head and neck squamous cell carcinoma - de Veij Mestdagh, Pieter D. (Clin Transl Radiat Oncol, 2019)
BACKGROUND: The vast majority of patients with head and neck squamous cell carcinoma (HNSCC) routinely undergo elective nodal irradiation (ENI) to both sides of the neck. Little is known about the extent to which bilateral ENI prevents regional failure (RF) and contralateral RF (cRF) in particular, while such knowledge is necessary to evaluate the results of more selective approaches like unilateral ENI. We investigated the rate and pattern of RF after bilateral ENI, the rate of cRF in the electively irradiated contralateral neck, and tried to identify risk factors for development of cRF. MATERIALS AND METHODS: Retrospective cohort study of a consecutive series of 605 patients with T1-4N0-3 HNSCC treated between 2008 and 2017 with primary (chemo)radiation and bilateral ENI. RESULTS: Median follow-up was 43 months (range 1.4–126). Three-year cumulative incidence of RF was 12.7%. Three-year cumulative incidences of ipsilateral RF (iRF) and cRF were 10.6% and 2.8%, respectively. All cRF occurred within the electively treated volume. Salvage treatment was possible in 65% and 59% of patients with iRF and cRF, respectively (p = 0.746). The 3-year overall survival rates after RF in patients with iRF and cRF were 27.4% and 41.2%, respectively (p = 0.713). Three-year cancer-specific survival rates were 31.6% and 48.1%, respectively (p = 0.634). In multivariate analysis, no significant predictive factors were identified for cRF after bilateral ENI. CONCLUSION: Contralateral regional failure is rare, but still occurs in 2.8% of patients treated with bilateral ENI. The possibilities for salvage treatment, the rates of overall survival and cancer-specific survival were comparable to patients with iRF.